Terminological and conceptual dilemma: strategies and processes as elicited through verbal reports on reading - Konieczna, Anna (Glottodidactica, 2011)
The paper analyses the ways in which the terms processes and strategies are defined within literature reporting verbal protocols on reading. The main argument presented concerns the fact that distinguishing between the two terms in not always based on the same criteria.